Validation of a Biofeedback System for Wheelchair Propulsion Training. (5th October 2011) - Guo, Liyun; Kwarciak, Andrew M.; Rodriguez, Russell; Sarkar, Nilanjan; Richter, W. Mark
Abstract : This paper describes the design and validation of the OptiPush Biofeedback System, a commercially available, instrumented wheel system that records handrim biomechanics and provides stroke-by-stroke biofeedback and targeting for 11 propulsion variables. Testing of the system revealed accurate measurement of wheel angle (0.02% error), wheel speed (0.06% error), and handrim loads. The maximum errors in static force and torque measurements were 3.80% and 2.05%, respectively. Measured forces were also found to be highly linear (0.985 < slope < 1.011) and highly correlated to the reference forces ( r 2 > .998). Dynamic measurements of planar forces (F x andF y ) and axle torque also had low error (−0.96 N to 0.83 N for force and 0.10 Nm to 0.14 Nm for torque) and were highly correlated ( r > .986) with expected force and torque values. Overall, the OptiPush Biofeedback System provides accurate measurement of wheel dynamics and handrim biomechanics and may be a useful tool for improving manual wheelchair propulsion.